Environmental flotation engineering - Wang, Lawrence K.; Wang, Mu-Hao Sung editor; Shammas, Nazih K.; Aulenbach, Donald B. A (Cham, Switzerland Springer, 2021)
This volume covers topics on humanitarian engineering education of the Lenox Institute of Water Technology and recent advances in potable water and wastewater flotation processes. The specific advancements covered include: chemical coagulation and precipitation enhancements, first wave of flotation advancement for potable water treatment, second wave of flotation technology advancement for wastewater treatment, innovative circular gravity flotation, fiber detection, fiber separation, independent physicochemical wastewater treatment systems, primary flotation clarification, secondary flotation clarification, tertiary treatment, activated sludge and flotation wastewater treatment, cold weather wastewater conditions, operation and performance of the AquaDAF process system, operation and performance of the Clari-DAF process system, water purification, spectrophotometric determination of dissolved proteins, biological and physicochemical sequencing batch reactors, and sedimentation and flotation comparisons. The book will be of value to advanced undergraduate and graduate students, to designers of flotation systems, and to scientists and researchers.
Electronic reproduction
Keywords: Water -- Purification -- Dissolved air flotation; Sewage -- Purification -- Flotation; Electronic books